Periodontal Ligament Stem Cells in the Periodontitis Microenvironment Are Sensitive to Static Mechanical Strain - Jia Liu; Qiang Li; Shiyu Liu; Jie Gao; Wen Qin; Yang Song; Zuolin Jin (Stem Cells International)
During orthodontic treatment, periodontium remodeling of periodontitis patients under mechanical force was abnormal. We have previously confirmed the function impairment of periodontal ligament stem cells (PDLSCs) in the periodontitis microenvironment which might be involved in this pathological process. However, the response of PDLSCs in periodontitis microenvironment to mechanical force remains unclear. Therefore, in the present study, we introduced a Flexcell tension apparatus and investigated the response of PDLSCs obtained from periodontal tissues of periodontitis patients (PPDLSCs) and of those obtained from healthy periodontal tissues (HPDLSCs) to different magnitudes of static mechanical strain (SMS). PPDLSCs showed increased proliferation, decreased osteogenic activity, activated osteoclastogenesis, and greater secretion of inflammatory cytokines. Different magnitudes of SMS exerted distinct effects on HPDLSCs and PPDLSCs. An SMS of 12% induced optimal effects in HPDLSCs, including the highest proliferation, the best osteogenic ability, the lowest osteoclastogenesis, and the lowest secretion of inflammatory cytokines, while the optimal SMS for PPDLSCs was 8%. Excessive SMS damaged PPDLSCs function, including decreased proliferation, an imbalance between osteogenesis and osteoclastogenesis, and an activated inflammatory response. Our data suggest that PPDLSCs are more sensitive and less tolerant to SMS, and this may explain why mechanical force results in undesirable effects in periodontitis patients.